Self-advocacy in Sweden—an analysis of impact on daily life and identity of self-advocates with intellectual disability - Mineur, Therése (Cogent social sciences, 2017)
Self-determination and the ability to express opinions and preferences are fundamental to all people. Some people with intellectual disability no longer accept a subordinated role as disabled and new self-advocacy groups have evolved. The aim of this study was to analyse the meaning and importance of engagement in a self-advocacy group for self-advocates daily life and identity. An interpretative abductive approach was used to analyse data from interviews with 26 self-advocates from six self-advocacy groups in Sweden in relation to the theoretical concepts; recognition, social capital, culture capital and self-determination. The key finding is that the vast majority of the participants experienced a changed self-perception, as more skilled, social and confident people, depending on group affiliation, their personal engagement and positions within the group. The conclusion is that self-advocacy is important for daily life and identity of people with intellectual disability. The self-organized movements indicate an important change in society and the results are of importance not only for the target group but for shaping future support and treatment from society of people with intellectual disability.